A study of dermatoses in patients attending pediatric OPD in a tertiary care hospital of Gandhinagar, Gujarat, India - Gunjana, Geet; Upadhyay, Nisha (International Journal of Contemporary Pediatrics, 2017)
Background: Skin diseases in paediatric population are common all over the world. There is a wide variation in the presentation of Dermatoses in various studies. The variation among dermatoses can possibly be due to region of study, prevalent environmental factors, type of population studied, and hygiene and nutritional status and environmental factors. The objective of this study was to study prevalence, pattern of presentation and aetiologies of various dermatoses in paediatrics. Methods: A prospective, observational, single center study involving 500 patients of Dermatoses was carried out in a pediatric outpatient department. Detailed history, clinical presentation and other relevant parameter were recorded in a case record form and analyzed. Results: Majority of patients with dermatoses (39.40%) belong to age group of 6 - 16 years with male preponderance. Etiological analysis showed infections and infestations were most common dermatoses. Bacterial infection (184, 36.80%) was most common followed by viral (87, 17.40%), parasitic (51, 10.20%) and fungal (25, 5.00%) infection. Dermatitis was present in 30.6% patients. Diaper dermatitis (19 patients) was the commonest dermatitis present in infants while eczema and urticaria were the commonest dermatitis in school going children. Pyoderma was the commonest dermatoses in this study, present in 111 patients (22.20%) followed by varicella (14.40%), impetigo (12.80%); scabies (10.20%), eczema (10.20%) and urticaria (7.60%). Conclusions: Dermatoses in children are a wide spread problem which are responsible for significant morbidity in children. The high incidence of infections and infestations are possibly due to poverty, overcrowding, undernutrition, poor hygiene and lack of health education. Skin of the young children is more prone to develop skin disease.